Spatial Distribution of Local Sustainability Index in the Ciletuh-Palabuhanratu UNESCO Global Geopark Using Spatial Autocorrelation - Salsiah, Siti; Saizen, Izuru; Soetarto, Endriatmo; Pravitasari, Andrea Emma (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
The Ciletuh-Palabuhanratu UNESCO Global Geopark (CPUGG) is a geopark area that is also a tourist destination in Sukabumi, West Java, Indonesia. CPUGG is experiencing rapid regional development, which can be seen from the increase in tourist visitors, changes in land use from agricultural land to built-up areas, the rapid growth of infrastructure and facilities, and the emergence of various economic activities. This study aims to determine local sustainability performance based on the spatial distribution pattern of the local sustainability index (LSI) in CPUGG using a spatial autocorrelation approach. The results show that the CPUGG development is not evenly distributed yet. The spatial distribution pattern of the local sustainability index in economic, social, and environmental are clustered. Each clustering shows that each village influences the surrounding villages. So, increasing the economic, social, and environmental sustainability index in several villages with a low sustainability index is necessary. Good cooperation is needed between the government, society, and several stakeholders to improve economic, social, and environmental development in The Ciletuh-Palabuhanratu UNESCO Global Geopark, West Java, Indonesia.